Product Review Sentiment Analysis by Artificial Neural Network Algorithm - Astuti, Tri; Pratika, Irnawati (International Journal of Informatics and Information Systems, 2019)
Buying and selling and marketing goods and services are now done online. The online store provides facilities that enable its customers to provide review related products offered. The number of reviews received by the store, online sometimes does not allow the store online to analyze one by one. Thus, it takes the help of machines to assist in the analysis of such sentiments. Analysis of the sentiments of the review the product is done to help the shop get a general overview related to the level of consumer satisfaction. In this study, the ANN algorithm will be used to analyze sentiment for review. A product ANN algorithm used because it can provide high accuracy performance. This research resulted in a reasonably high accuracy performance is 88.2%.